A Schulman enters strategic partnership to commercialize masterbatch in Africa. Issue 9 (September 2016) - Unknown
Abstract : US-based A. Schulman Inc, an international producer of masterbatches, high-performance plastic compounds and resins, is targeting the expansion of its masterbatch footprint on the African continent via a strategic partnership with Snetor Chimie. The latter is charged with commercializing A. Schulman's complete range of white, black and coloured masterbatches and additives in the region. Headquartered in Courbevoie Cedex, France, Snetor Chimie is one of the leading distributors of plastics and chemical products in Africa.